The importance of temperature and viscosity effects for surfactant adsorption measurements made using the electrochemical quartz crystal microbalance - Ryu, Dong Y; Free, Michael L (Journal of colloid and interface science, 2003)
The measurement of adsorbed surfactant is important to fields such as corrosion inhibition, metal cleaning, and separation technologies. The electrochemical quartz crystal microbalance (EQCM) is an important tool that can be used to measure adsorbed surfactant. However, such measurements are subject to significant temperature and viscosity effects that must be appropriately considered. This paper discusses the effect of temperature and viscosity on EQCM measurements in solution environments and the ability of the EQCM to measure surfactant adsorption.